1995
DOI: 10.1289/ehp.95103582
|View full text |Cite
|
Sign up to set email alerts
|

A variety of environmentally persistent chemicals, including some phthalate plasticizers, are weakly estrogenic.

Abstract: Sewage, a complex mixture of organic and inorganic chemicals, is considered to be a major source of environmental pollution. A random screen of 20 organic man-made chemicals present in liquid effluents revealed that half appeared able to interact with the estradiol receptor. This was demonstrated by their ability to inhibit binding of 17 beta-estradiol to the fish estrogen receptor. Further studies, using mammalian estrogen screens in vitro, revealed that the two phthalate esters butylbenzyl phthalate (BBP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
377
1
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,089 publications
(396 citation statements)
references
References 51 publications
13
377
1
5
Order By: Relevance
“…The sum of studied compounds was thus 12 times higher in water from PET bottles compared to samples from glass bottles. Taken together, there is good analytical evidence for the migration of certain phthalates from PET food packaging materials, some of them well-known xenoestrogens (Jobling et al 1995). However, the estrogenicity reported in this study might also arise from unexpected compounds: Shotyk et al (2006) found antimony in up to 30 times higher concentrations in mineral water from PET compared to glass bottles and confirmed its leaching from PET (Shotyk and Krachler 2007), in whose manufacturing antimony trioxide is used as catalyst.…”
Section: Discussionsupporting
confidence: 62%
“…The sum of studied compounds was thus 12 times higher in water from PET bottles compared to samples from glass bottles. Taken together, there is good analytical evidence for the migration of certain phthalates from PET food packaging materials, some of them well-known xenoestrogens (Jobling et al 1995). However, the estrogenicity reported in this study might also arise from unexpected compounds: Shotyk et al (2006) found antimony in up to 30 times higher concentrations in mineral water from PET compared to glass bottles and confirmed its leaching from PET (Shotyk and Krachler 2007), in whose manufacturing antimony trioxide is used as catalyst.…”
Section: Discussionsupporting
confidence: 62%
“…Other food additives include camphor, 1,8-cineole (eucalyptol), citral, citronellal, cis-3-hexenol, heliotropin, hexanoic acid, menthol, phenylethyl alcohol, triacetin, and terpineol. Some of these may be implicated as oxidants or endocrine disruptors (Jobling et al, 1995).…”
Section: Food Additivesmentioning
confidence: 99%
“…The observed effects in fish include vitellogenin induction, abnormal development of gonads (Harries et al, 1997;Lye et al, 1997;Jobling et al, 2002) and secondary sexual characteristics (Batty and Lim, 1999;Xie et al, 2010), which have been linked to some estrogenic compounds in the effluents of sewage treatment plants (Harries et al, 1997;Jobling et al, 2002;Lye et al, 1997;Thorpe et al, 2003;Xie et al, 2010). These compounds include 4-t-octylphenol (4-t-OP), 4-nonylphenols (4-NP), bisphenol-A (BPA), estrone (E1), estradiol (E2) and triclosan (TCS), which have been demonstrated to have in vitro and/or in vivo estrogenic activities (Foran et al, 2000;Ishibahsi et al, 2004;Jobling and Sumpter, 1993;Jobling et al, 1995;Raut and Angus, 2010;Stasinakis et al, 2008). Therefore, it is essential to monitor these estrogenic compounds in aquatic environments in order to protect the ecosystem.…”
Section: Introductionmentioning
confidence: 99%